Een herdersknaap : een gedicht van Jan van het Kruis – kritisch bekeken - Waaijman, Kees (HTS teologiese studies, 2015)
A shepherd-boy: A poem by Saint John of the Cross – critical meaning. A shepherd-boy, written by Saint John of the Cross around 1584, is a pastoral poem, a common and widespread genre at the time. Although the poet could have drawn from various sources, direct borrowing does not appear to have been the case. The poem has five stanzas, each consisting of four lines, with eleven syllables per line (a cuartet, with enclosing rhyme: abba). In the superscription the poem is described as a song a lo divino, a poetic transposition that transforms a profane text ‘towards the divine’, within a Christian-religious framework. A shepherd-boy places itself within this poetic tradition, but in a unique way, because his transposition is not prompted by catechetical interests, but opts for a mystical perspective.